Curating the Painting Collection of the Presidential Palace of the Republic of Indonesia - Susanto, Mikke; Simatupang, GR. Lono L.; Haryono, Timbul (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
The Presidential Palace of the Republic of Indonesia's collection of art objects was started by Indonesia's first president, Sukarno. Today, this collection includes more than 2,500 paintings, and as such this institution has acted like a museum. Throughout the tenure of Indonesia's seven presidents, this collection has experienced diverse stories related to its curation by various individuals over time. This article will focus on the historical issues of this collection's curation using qualitative research methods, in the hopes of revealing various curatorial issues. More specifically, the qualitative research conducted for this study is related to art history. This articleutilizes theory related to curation to discuss a number of topics, ranging from the role of the individuals responsible for the collection (i.e. curators), the systems of caring for and selecting works (curation), and the curatorial practices that have occurred until now. Elaborating on a number of archival documents related to this collection, this article examines the work of the collection's curators, from inventorization to opening the collection to the public. Over the course of 70 years, the Presidential Palace's collection has undergone various forms of curation, including acquisition, documentation, preservation, and exhibition. This research concluded that the role of the curator is very important and causes the collection to be preserved and more valuable. As such, this article suggests a special museum related to the paintings within the palace collection.